Discovery of a pulsar-powered bow shock nebula in the Small Magellanic Cloud supernova remnant DEM S5. Issue 2 (8th April 2019) - Alsaberi, Rami Z E; Maitra, C; Filipović, M D; Bozzetto, L M; Haberl, F; Maggi, P; Sasaki, M; Manjolović, P; Velović, V; Kavanagh, P; Maxted, N I; Urošević, D; et al.
ABSTRACT: We report the discovery of a new Small Magellanic Cloud pulsar wind nebula (PWN) at the edge of the supernova remnant (SNR) DEM S5. The pulsar powered object has a cometary morphology similar to the Galactic PWN analogues PSR B1951+32 and 'the mouse'. It is travelling supersonically through the interstellar medium. We estimate the pulsar kick velocity to be in the range of 700–2000 km s −1 for an age between 28 and 10 kyr. The radio spectral index for this SNR–PWN–pulsar system is flat (–0.29 ± 0.01) consistent with other similar objects. We infer that the putative pulsar has a radio spectral index of –1.8, which is typical for Galactic pulsars. We searched for dispersion measures up to 1000 cm −3  pc but found no convincing candidates with an S/N greater than 8. We produce a polarization map for this PWN at 5500 MHz and find a mean fractional polarization of P  ∼ 23 per cent. The X-ray power-law spectrum (Γ ∼ 2) is indicative of non-thermal synchrotron emission as is expected from PWN–pulsar system. Finally, we detect DEM S5 in infrared (IR) bands. Our IR photometric measurements strongly indicate the presence of shocked gas that is expected for SNRs. However, it is unusual to detect such IR emission in an SNR with a supersonic bow shock PWN. We also find a low-velocity H i cloud of ∼107 km s −1 that is possibly interacting with DEM S5. SNR DEM S5 is the first confirmed detection of a pulsar-powered bow shock nebula found outside the Galaxy.